Broadband optical access networks : emerging technologies and optical-wireless convergence - Kazovsky, Leonid G. (Hoboken, N.J. : Wiley-Interscience, 2011)
"Broadband optical access network is an ideal solution to alleviate the first/last mile bottleneck of current Internet infrastructures. Richly illustrated throughout to help clarify important topics, Broadband Optical Access Networks covers the architectures, protocols enabling technologies of broadband optical access networks, and all current and future competing technologies for access networks. This comprehensive work presents the evolution of optical access networks, including reach extension, bandwidth enhancement, and discusses the convergence of optical and wireless technologies for broadband access, making it an invaluable reference for researchers, electrical engineers, and graduate students"--
"This comprehensive reference covers the architectures, protocols enabling technologies of broadband optical access networks and all current and future competing technologies for access networks"--
Includes bibliographical references.
Keywords: Optical communications; TECHNOLOGY & ENGINEERING / Telecommunications